Analisis Kondisi Sosial Dan Ekonomi Petani Bunga Krisan Di Kelurahan Kakaskasen Dua Kecamatan Tomohon Utara Kota Tomohon - Saamad, Velty Neiscasari; Memah, Melsje Yelly; Wariki, Barce A.F. (AGRI-SOSIOEKONOMI, 2024)
The purpose of the study was to analyze the socio-economic conditions of flower chrysanthemum farmers in Kakaskasen Two urban village, North Tomohon Sub-district, Tomohon City. This research was conducted from September to November 2023. The data collected in this study were primary data and secondary data. Sampling was done by simple random sampling method which is as many as 30 respondents. Data analysis used in this research is descriptive analysis method. The results showed that the socio-economic conditions of chrysanthemum farmers in Kakaskasen Two urban village, North Tomohon Sub-district, Tomohon City, from social conditions are respondent farmers are able to build good relationships with their communities, namely religious associations, family, friends and the surrounding community. In economic conditions, the production of chrysanthemums provides a large profit for farmers. The division of social and economic time of respondent farmers is approximately 15.73 hours and 8.27 hours in a day.